Basin record of Mesozoic tectonic events in Southeast South China - Pang, Chongjin (Curtin University, 2014)
Through the first detail geochronological, sedimentological and stratigraphic analysis, this thesis provides new insights into the depositional and tectonic history of the Late Triassic to Middle Jurassic intracontinental basin in southeastern South China, and discusses the geodynamic processes that controlled rapid continental vertical movements. Stratigraphic evolution, basin filling pattern and accompanied magmatism are interpreted to be the consequence of a flat subduction and subsequent delamination and foundering of an oceanic plateau.